2013
DOI: 10.1182/blood.v122.21.3782.3782
|View full text |Cite
|
Sign up to set email alerts
|

Requirement For CDK6 In MLL-Rearranged Acute Myeloid Leukemia

Abstract: Chromosomal rearrangements involving the H3K4 methyltransferase MLL trigger aberrant gene expression programs in hematopoietic stem and progenitor cells and give rise to an aggressive subtype of acute myeloid leukemia (AML) that is associated with intermediate or poor survival. Insights into MLL fusion-mediated leukemogenesis have not yet translated into better therapies in the clinic, in part because mutant MLL is difficult to target directly and it is incompletely understood which of the genes affected by al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Pharmacological inhibition of CDK6 by the CDK4/6 inhibitor PD‐0332991 (palbociclib), unlocks the blocked differentiation and reduces the leukemic phenotype in human AML cell lines. These findings proposed that CDK6 inhibition provides a clinically applicable therapeutic opportunity for MLL‐rearranged leukemia 38 . A proliferation advantage of leukemic cells through MLL fusion‐driven upregulation of CDK6 has also been shown in MLL‐rearranged infant ALL 39…”
Section: Cdk6 In Hematologic Malignanciesmentioning
confidence: 88%
“…Pharmacological inhibition of CDK6 by the CDK4/6 inhibitor PD‐0332991 (palbociclib), unlocks the blocked differentiation and reduces the leukemic phenotype in human AML cell lines. These findings proposed that CDK6 inhibition provides a clinically applicable therapeutic opportunity for MLL‐rearranged leukemia 38 . A proliferation advantage of leukemic cells through MLL fusion‐driven upregulation of CDK6 has also been shown in MLL‐rearranged infant ALL 39…”
Section: Cdk6 In Hematologic Malignanciesmentioning
confidence: 88%
“…As a serine/threonine kinase, CDK6 is indispensable for the passage of G1 to S phase by phosphorylating retinoblastoma protein 11 . Recently, several studies have revealed that in addition to regulating the cell cycle, CDK6 plays essential roles in apoptosis, 12 reprogramming of cancer cell metabolism, 13 and self‐renewal ability of leukaemia stem cell (LSC) 14 . For example, CDK6 is an indispensable downstream effector in MLL‐rearranged AML, and knockdown of CDK6 reduces the self‐renewal LSC in MLL arrangements‐transformed mouse leukaemia 14 .…”
Section: Introductionmentioning
confidence: 99%
“…60 Furthermore, CDK6 plays a crucial role in several myeloid diseases, including Jak2 V617F1 myeloproliferative neoplasm, chronic myeloid leukemia, and acute myeloid leukemia, by regulating stem cell quiescence, apoptosis, differentiation, and cytokine secretion. 53,61,62 Using the long-term culture system, it was possible to generate HPC LSKs from the transgenic mouse line Cdk6 2/2 , which represents a powerful tool to analyze specific functions of CDK6 in progenitor cells and allows mechanistic and therapeutic studies tailored specifically to leukemic stem/progenitor cells.…”
Section: Introductionmentioning
confidence: 99%